Vulnerability of Elderly Women: Victim of Gender Discrimination - Subir Kumar Roy (Hasanuddin Law Review, 2017)
The life cycle of human being completes with the process of aging but we fail to realize this simple arithmetic of life and often consider our elders as a burden for us. They are compelled to compromise with their dignity and integrity and forced to live at the mercy of their own nearest and dearest. When we talk about elderly women their position is more appalling than their male counterpart due to this male chauvinism which tries to regulate every affair of the life of the people. Under the alibi of protection and security of women they are subjected to the violent gender discrimination and compelled to live and lead their life at the fingertips of a male. The women in especially in third world countries are considered as a tool of procreation of child and all her activities and qualities of life are relegated with the household course. Across the globe the male tendency is to regulate Women’s ownership and control of property, resources created by her own labor, education and information and even her reproductive abilities and sexualities with an intention to jeopardize and throttled down the rights of the women. Women bear this status till her last breath and hence, it is axiomatic that how vulnerable their position is.